Helicase loading: How to build a MCM2-7 double-hexamer - Riera,A; Tognetti,S; Speck,C (Seminars in Cell and Developmental Biology, 2014)
A central step in eukaryotic initiation of DNA replication is the loading of the helicase at replication origins, misregulation of this reaction leads to DNA damage and genome instability. Here we discuss how the helicase becomes recruited to origins and loaded into a double-hexamer around double-stranded DNA. We specifically describe the individual steps in complex assembly and explain how this process is regulated to maintain genome stability. Structural analysis of the helicase loader and the helicase has provided key insights into the process of double-hexamer formation. A structural comparison of the bacterial and eukaryotic system suggests a mechanism of helicase loading. © 2014 Elsevier Ltd.